Male-female young learners' perspective on the use of crossword puzzle aids to enrich their vocabulary - Berliana, Nina; Friatin, Lilies Youlia; Said, Iskhak (Journal of English Education Program (JEEP), 2025)
Vocabulary is very essential in communication, but the fact indicates that lack of vocabulary still hampers the effective communication. This paper investigates the perspective of young female and male learners on the application of Crossword puzzle aids to enrich their vocabulary. The goal of this study is to find out male and female young learners’ perspectives on the use of crossword puzzle aids to enrich their vocabulary. The research design of this current study uses the type of case study so that twenty-one students from grade seven in a Junior High School in Ciamis were involved. The data come from a questionnaire which deals with the perspective of young female and male learners on the application of Crossword puzzle aids to increase their vocabulary. The close-ended questionnaire data are then analyzed and proceeded. The result shows that the young female and male learners perceive the application of Crossword puzzle as the aids to enrich their vocabulary. In learning, vocabulary can enrich their vocabulary with different skills based on gender because gender differences can influence young and female learners to increase their vocabulary skills. Besides that, Crossword puzzle aids are interesting, gives many opportunities, and helps male and female learners to receive and understand the vocabulary more easily. Further, using crossword puzzles aids learning vocabulary and can increase the achievement of male and female young learners. Also, it makes change towards the situations such as playing games when learning vocabulary process.